Penentuan Indikator Jumlah Mahasiswa Optimal Pada Program Studi di Fakultas Teknik di Universitas Insan Cendikia Mandiri d/h Universitas Bandung Raya - alam avrianto; Kiki Abdul Muluk (Sainteks: Jurnal Sain dan Teknik, 2020)
Finance has a very important role in supporting the sustainability of a university's activities. In the current condition at the University of Bandung Raya, the number of students has decreased which will affect their income level. What is done by the university is to find as many students as possible in each available study program. Based on the results of the study, it shows that this results in a higher level of financial expenditure than income due to the small number of students who are spread across 4 existing study programs. Based on the results of the calculation, it is found that if the university will benefit based on the existing conditions, namely by only focusing on 1 undergraduate study program with a total of 150 students.